A Study on the Effect of Different Interconnection Materials (Wire and Bond Pad) on Ball Bond Strength after Temperature Cycle Stress - A. P., Puvanasvaran (2012)
Interconnection material is a important element in the industry. This study is investigate the effect of different interconnection materials on ball bond strength and study the effect of temperature cycling stress test on the ball bond strength. The literature review is based on comprehensive literature review from previous study. The strength on different interconnection materials of wire (gold and aluminum) and bond pad (copper and aluminum) after temperature cycle is investigated by using DMAIC methodology. The study is started with the reliability test with various Temperature Cycle (TC) stress and Failure Analysis testing was carried out to collect the wire pull strength value and ball shear strength value of different device.